The Integrated Role of Multidisciplinary Healthcare Teams in Enhancing Quality of Care and Patient Outcomes in Hospitals - Asiri, Mohammed Ali Abdullah; Almutairi, Hakem Masad; Alyousef, Ibrahim Hussain Yousef; Al Sharari, Thamer Salah; Alqahtani, Khaled Mohammed Said; Aljalis, Mohammed Abdullah Saad; Alrashdi, Mohammed Alfulayhi; Alshahrani, Ahmad Saeed Alwaked; Alalyani, Saad Abdullah Dakhilallah; Al Sharai, Mohammed Ali (Journal of Ecohumanism, 2025)
Multidisciplinary healthcare teams play a pivotal role in enhancing the quality of care and improving patient outcomes within hospital settings. As modern healthcare systems evolve toward more patient-centered and integrated service models, collaboration among diverse healthcare professionals—including physicians, nurses, pharmacists, laboratory specialists, radiology technologists, physical and respiratory therapists, dietitians, and medical social workers—has become essential. This paper examines the collaborative contributions of multidisciplinary teams in optimizing clinical decision-making, reducing medical errors, improving treatment accuracy, and enhancing patient safety and satisfaction. Using a descriptive analytical approach, relevant literature and recent evidence-based studies were reviewed to assess the strategic impact of interprofessional healthcare collaboration. Findings indicate that integrated teamwork leads to faster recovery rates, reduced hospitalization periods, improved continuity of care, and greater patient trust in healthcare services. The study highlights the importance of strengthening communication among healthcare professionals, investing in continuous professional development, and adopting structured multidisciplinary care models. It is recommended that healthcare institutions implement policies that support interprofessional cooperation to ensure high-quality patient care and achieve sustainable improvement in hospital performance and health outcomes.